In Situ Formation of Multiple Schottky Barriers in a Ti(3)C(2)MXene Film and its Application in Highly Sensitive Gas Sensors - Choi, Junghoon; Kim, Yong-Jae; Cho, Soo-Yeon; Park, Kangho; Kang, Hohyung; Kim, Seon Joon; Jung, Hee-Tae (WILEY-V C H VERLAG GMBH, 2020)
The main gas-sensing mechanisms of 2D materials are surface charge transfer by analytes and Schottky barrier (SB) modulation at the interface between the metallic and semiconducting surfaces. In particular, dramatic differences in the gas-sensing performances of 2D materials originate from SB modulation. However, SB sites typically exist only at the interface between the semiconducting channel material and the metal electrode. Herein, in situ formed multiple SBs in a single gas-sensing channel are demonstrated, which are derived from the heterojunction of metallic Ti(3)C(2)and semiconducting TiO2. In stark contrast with previous techniques, edge-oxidized Ti(3)C(2)flakes are synthesized by solution oxidation, allowing the uniform formation of TiO(2)crystals on all flakes that comprise the gas sensing channel. Oxidized colloidal solutions are subjected to vacuum filtration to automatically form SB sites at the multiple inter-flake junctions in both the outer surface and inner bulk regions of the film. The TiO2/Ti(3)C(2)composite sensor shows 13.7 times higher NO(2)sensitivity as compared with pristine Ti(3)C(2)MXene, while the responses of the reducing gases are almost unchanged. The results suggest a new strategy for improving gas-sensing performance by maximizing the density of SB sites through a simple method.
Keywords: MOS2; PERFORMANCE; MXENE; NANOMATERIALS; ANATASE